Eigentlichkeit: zum Verhältnis von Sprache, Sprechern und Welt - Brinker-von der Heyde, Claudia; Kalwa, Nina; Klug, Nina-Maria; Reszke, Paul (De Gruyter, 2015)
The volume explores conceptual, methodological, and practical issues related to ideal of authenticity in communication - that is, speech and writing that appropriately relates to the objective world and at the same time communicates the true intentions of the speaker or author. --